The last time she saw him : a novel [large type] - White, Kate, 1950- (Harper Large Print, an imprint of HarperCollinsPublishers, 2024)
It's summer in New York City, but Kiki Reed isn't feeling very sunny. She recently broke off her engagement to Jamie Larsson, a great guy, but just not "the one." And although she knows it was for the best, she feels guilty for hurting him. When Kiki accepts an invitation to a party at a friend's Connecticut country house, she knows Jamie will be there, too, but decides to get their first interaction over with. When they come face to face, their exchange is brief and pleasant, a huge relief for her. Then, as the party is winding down, a shot rings out. The few remaining guests run outside to find Jamie inside his car, dead from a gunshot wound. Shocked and grieving, Kiki soon hears that the police are leaning toward ruling it a suicide, but she knows that Jamie was moving on from their breakup, and truly doubts that he's taken his own life. Determined to find the truth, she rents a house in the area to look for the missing link that will get the police to take her seriously. But as she peels away the layers, she uncovers something far more sinister than she had ever imagined, and it may be her life on the line next.